Discovery of a Novel CHD7 CHARGE Syndrome Variant by Integrated Omics Analyses - Granadillo, Jorge L (Am J Med Genet A, 2020)
BACKGROUND: CHD7 pathogenic variants are identified in more than 90% of infants and children with CHARGE syndrome. Approximately 10% of cases have no known genetic cause identified. METHODS: We report a male child with clinical features of CHARGE syndrome and non-diagnostic genetic testing that included chromosomal microarray, CHD7 sequencing and deletion/duplication analysis, SEMA3E sequencing, and trio Exome and Whole Genome Sequencing. We used a comprehensive clinical assessment, genome-wide methylation analysis (GMA), reanalysis of Whole Genome Sequencing (WGS) data, and CHD7 RNA studies to discover a novel variant that causes CHD7 haploinsufficiency. RESULTS: The 7-year-old Hispanic male proband has typical phenotypic features of CHARGE syndrome. GMA revealed a CHD7-associated epigenetic signature. Reanalysis of the WGS data with focused bioinformatic analysis of CHD7 detected a novel, de novo 15 base pair deletion in intron 4 of CHD7, (c.2239–20_2239–6delGTCTTGGGTTTTTGT (NM_017780.3)). Using proband RNA, we confirmed that this novel deletion causes CHD7 haploinsufficiency by disrupting the canonical 3’ splice site and introducing a premature stop codon. CONCLUSION: Integrated genomic, epigenomic, and transcriptome analyses discovered a novel CHD7 variant that causes CHARGE syndrome.